Erythrocyte Osmotic Fragility and Excitability Score in Rabbit fed Hibiscus Sabdariffa in Graded Level (Nigerian Journal of Physiological Sciences, 2021)
Summary: This study was conducted for 10 weeks with the aim of investigating the erythrocyte membrane integrity as measured by erythrocyte osmotic fragility and excitability scores of rabbits fed graded level of Hibiscus sabdariffa calyx (HSC). Twenty weaners’ rabbit of both sexes were used for the study and were placed on four experimental diets which contain the following percentages of HSC 0 %, 25 %, 50 %, 75 %, as feed additive and were added at 0 g, 62.5 g, 125 g, 187.5 g designated as T1, T2, T3 and T4 experimental diets. Excitability scores were measured weekly as described by Voisnet et al. (1997). At the end of the experiment, the rabbits were slaughtered by severing the jungular vein. A Blood sample (2 ml) was collected from each rabbit into sampled bottles, containing the Na EDTA as anticoagulant for hematological analysis. Packed cell volume (PCV) Haemoglobin concentration (Hb), Total red blood cell (RBC) count, Total leukocyte count as well as differential leukocyte was determined using standard method. The percentage haemolysis recorded at 0.3 % to 0.8 % was significantly (P < 0.05) higher in rabbits in T1 compared to the remaining 3 diets. The result of excitability score shows that rabbit on diet 1 and 2 had a lower value which was significantly (P < 0.05) lower than rabbits on diets 3 and 4 with a value of 65.5 ± 5.0 and 70.00 ± 5.50 % respectively. In conclusion this study demonstrated for the first time that chronic administration of HSC improves haematological parameters, brain mood and function as well as maintaining erythrocyte membrane integrity.